PENGARUH TERAPI ISOMETRIC HANDGRIP EXERCISE TERHADAP TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI PUSKESMAS PEMBINA PALEMBANG - R.A Fadila; Ary Izwar Romansyah (Jurnal Kesehatan dan Pembangunan, 2026)
Hypertension or high blood pressure if the blood vessels are more than (140/90 mmHg). According to the World Health Organization (WHO), hypertension affects 1.28 billion people worldwide between the ages of 30 and 79 years. The purpose of the study was to determine the effect of isometric handgrip exercise therapy on blood pressure in the elderly with hypertension at the Palembang Pembina Health Center in 2024. The research method used pre-experimental designs with the One Group Pretest Postest approach. The population in this study were all elderly people suffering from hypertension at the Palembang Pembina Health Center with a sample size of 30 respondents using purposive sampling. The results of the study obtained the frequency distribution of systolic blood pressure before the intervention, most of whom experienced moderate hypertension as many as 21 respondents (70%), while after the intervention most of whom experienced mild hypertension as many as 22 respondents (73.3%). The frequency distribution of diastolic blood pressure before the intervention was mostly experiencing severe hypertension as many as 13 respondents (43.3%) and after the intervention most experienced mild hypertension as many as 16 respondents (53.4%). The results of the statistical test showed the effect of isometric handgrip exercise therapy on systolic blood pressure (p.value = 0.000) and diastolic blood pressure (p.value = 0.000) in hypertensive patients at the Pembina Palembang Health Center in 2025. Suggestions are expected to develop policies to implement isometric handgrip exercise activities as one of the non-pharmacological therapies for patients with hypertension in addition to drug therapy that has been given to hypertension sufferers